SUBSYSTEM OF VISUALIZATION OF THE KNOWLEDGE BASE OF THE EXPERT SYSTEM OF TECHNICAL DIAGNOSTICS - Dubrovin, V. I.; Deinega, L. Y. (Radio Electronics, Computer Science, Control, 2024)
The automated subsystem of visualization of knowledges base, application of which simplifies work of user with a expert system, is presented in the article. The structure of knowledges representation, functional possibilities of subsystem and example of its use, is resulted.